Brain Tumor, Pheochromocytoma, and Pregnancy: A Case Report of a Cesarean Delivery in a Patient With Von Hippel–Lindau Disease. Issue 8 (15th October 2019) - Burnette, Michelle S.; Mann, Taylor S.; Berman, David J.; Nguyen, Truc-Anh T.
Abstract : A young woman first diagnosed with von Hippel–Lindau disease (VHL) during pregnancy underwent an uncomplicated cesarean delivery despite having multiple classic VHL tumors, including a large cerebellopontine brain mass and vasoactive pheochromocytoma. Patients with VHL may have multiple tumors of the central nervous system and viscera that greatly impact anesthetic management. This case highlights the anesthetic considerations for a parturient with pheochromocytoma and elevated intracranial pressure, as well as the importance of a multidisciplinary team approach.